2023
DOI: 10.3390/curroncol30030264
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible to Notice the Unmet Non-Medical Needs among Cancer Patients? Application of the Needs Evaluation Questionnaire in Men with Lung Cancer

Abstract: Background: Lung cancer is the most common cause of cancer death worldwide. It is the most frequently diagnosed cancer in men. Lung cancer causes not only physical symptoms related to the disease itself and its treatment but also numerous mental, social and spiritual problems. The aim of the study was to assess non-medical needs among male lung cancer patients during oncological treatment. Materials and Methods: The study was conducted on a group of 160 men (mean age 67 years) treated for lung cancer from June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Cognitive Emotion Regulation Questionnaire (CERQ), another focal point of the study, showed that cancer patients were more prone to self-blame, rumination, and catastrophizing, while demonstrating lower scores in adaptive strategies like positive refocusing and positive reappraisal. The inclination to catastrophize, coupled with tendencies for self-blame, can augment feelings of despair and powerlessness, further eroding their psychological well-being [11,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive Emotion Regulation Questionnaire (CERQ), another focal point of the study, showed that cancer patients were more prone to self-blame, rumination, and catastrophizing, while demonstrating lower scores in adaptive strategies like positive refocusing and positive reappraisal. The inclination to catastrophize, coupled with tendencies for self-blame, can augment feelings of despair and powerlessness, further eroding their psychological well-being [11,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…For example, lung cancer is a leading cause of cancer-related mortality (Sung et al 2021 ). Patients diagnosed with lung cancer often have a higher burden of symptoms than patients with other prevalent cancers and are less likely to receive support to manage these symptoms (Osowiecka et al 2023 ). PA has many benefits for the physical and mental health of those diagnosed with lung cancer (Teba et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%